2021
DOI: 10.1016/j.jvscit.2021.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Giant abdominal aortic aneurysms

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…In our study, only COPD was significantly more prevalent in patients with a large AAA. The obtained results are in accordance with the literature data showing that atherosclerotic changes and cardiovascular diseases are the most common comorbidities among patients with aortic aneurysm disease [17]. Jones W. et al [11], found a lower prevalence of comorbidities in patients with a small AAA, which can be explained by the selection of patients.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, only COPD was significantly more prevalent in patients with a large AAA. The obtained results are in accordance with the literature data showing that atherosclerotic changes and cardiovascular diseases are the most common comorbidities among patients with aortic aneurysm disease [17]. Jones W. et al [11], found a lower prevalence of comorbidities in patients with a small AAA, which can be explained by the selection of patients.…”
Section: Discussionsupporting
confidence: 91%
“…3 E, F). Per patient, the percentual underestimation of the CT volume by US is mostly constant with increasing size of the partial volume region, with an average of 11[ 5 8 ] % for volumes of 30 mm long.…”
Section: Resultsmentioning
confidence: 99%
“…There is however quite some heterogeneity in the progression of the disease, with some AAAs showing no growth for several years, or even shrinkage, while other AAAs grow as much as 1.3 cm/year [ 3 5 ]. Furthermore, there is variation in the diameter at which rupture occurs between patients: some smaller abdominal aneurysms of less than 5 cm rupture [ 6 ], while other larger aneurysms stay stable, even up to diameters of 20 cm [ 7 , 8 ]. These differences in growth and risk of rupture might be related to differences in the way that the aortic wall adapts to the changes in wall deformation as well as the load (pressure, blood flow pattern) it experiences while the AAA grows [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The repair of type II endoleak involves coil embolization of the blood vessels that are feeding the aneurysmal sac. Different imaging methods like CT, ultrasound (US), and magnetic resonance imaging (MRI) have been described for surveillance [ 5 ]; however, there is no clear consensus regarding how often the surveillance [ 6 ], and the benefit of early intervention vs continuous surveillance [ 2 ]. There are different studies that incline toward either approach.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal aortic aneurysms (AAA) are considered large when they exceed >6cm, and giant when they exceed >10cm in the maximum transverse diameter [ 1 ]. Giant AAAs are rare, with only a very few cases described as larger than 14cm [ 2 ]. Thoracic and abdominal AAAs can be successfully repaired through endovascular aneurysm repair (EVAR) or open surgery [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%